Study of the Potential of Historical Sitesand Tourist Destinations in the Vietnamese Village on Galang Island in Supporting Regional - Irawan, Jhoni; Sidabutar, Yuanita FD (Borong Newinera Publisher, 2025)
This study aims to trace the history of Galang Island, located in the Riau Islands Province, Indonesia, and once served as a shelter for refugees from Vietnam. From 1979 to 1996, the area known as Kampung Vietnam became a pivotal point in the history of international refugee management in Indonesia. For more than ten years, around 250,000 Vietnamese refugees lived in this area seeking safety from conflict and political instability in their country. Their presence influenced unique social interactions and cultural dynamics, both among the refugees and with the local community. Through this study, it is hoped that deeper insights can be gained into the social and cultural influences of the refugee community, as well as identifying steps to preserve the historical sites that are now part of the human heritage on Galang Island.